Morphometric Studies on Buffalo Ovary and Corpus Luteum during the Luteal Phase of Estrous Cycle and Pregnancy - Sachan, Vikas; Kumar, Brijesh; Singh, Avaneesh Kumar; Yadav, Dileep Kumar; Patel, Akhil (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Per rectal examination is the most adapted technique to diagnose pregnancy in large ruminants, particularly the palpation of the corpus luteum in buffalo is of great significance. The present study investigated the basic morphological differences between the ovaries along with corpus luteum of the pregnant buffalo and non-pregnant buffalo in the luteal phase of the estrous cycle. For the purpose, ten pregnant (60-70 days of gestation) and ten non-pregnant genitalia (11-17 days of estrous cycle) with the corpus luteum were obtained from freshly slaughtered buffaloes at local abattoir. Morphological parameters such as length, width, weight and thickness of the ovary were measured. Vasculature, colour, length, diameter and weight of the corpus luteum were also recorded. Morphological parameters of right ovaries as well as CL were higher in pregnant genitalia than in non-pregnant ones. Pregnancy CL was more pinkish (more vascularization), well embedded in the ovary (as a diffused swell portion without crown-like elevation) without a demarcated point of ovulation. The study concludes that there were well-demarcated morphological differences between pregnant and non-pregnant buffalo ovary and corpus luteum.